Thesis to qualify for the Title of Psychologist that contribute to psychotherapeutic work. Universidad de Chile 1994 to 1998 - Moncada Arroyo, Laura; Costas Moreno, Andrés; Olivos Balmaceda, Pedro (Revista de Psicología, 1999)
This articles shows the results of a comprehensive review of the thesis done by undergraduate's students in order to obtain their title of Psychologist in the University of Chile between the years 1994 to 1998. The review is focused in the thesis reñated to psychotherapy. The theoretical frames, type of sttudy, age and gender of the population and the contribution of the thesis are described. Creatives psychological approaches. Originals works are emphasized.